1970
DOI: 10.1088/0022-3727/3/9/321
|View full text |Cite
|
Sign up to set email alerts
|

Electric field distribution in a cylindrical TM010 microwave cavity with end holes and a glass tube

Abstract: A perturbation method is used for the experimental study of the effects of end holes and a glass tube on the electric field configuration in a cylindrical TM010 microwave cavity at a wavelength of 3 cm. The radius of the cavity, the radius of the end holes in each end plate and the thickness of the glass tube are comparable. The results show that the electric field intensity and configuration in the plane of the end holes (i.e. in the interacting space of a plasma with the cavity) are highly perturbed. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The theoretical electric field intensity distribution in a closed, unperturbed (without the holes and a glass tube) cylindrical T M 010 microwave cavity is proportional to the zero-order Bessel function in the radial direction. In our previous paper (Pipišková, and Lukáč [34]) we have shown that a glass tube affects the electric field configuration and the electric field intensity in a cylindrical T M 010 microwave cavity which in turn modifies the absolute electron density value determination. We have carried out the same measurement in the first experimental dual mode set up, for the S-band microwave range.…”
Section: Electron Density Measurementsmentioning
confidence: 97%
“…The theoretical electric field intensity distribution in a closed, unperturbed (without the holes and a glass tube) cylindrical T M 010 microwave cavity is proportional to the zero-order Bessel function in the radial direction. In our previous paper (Pipišková, and Lukáč [34]) we have shown that a glass tube affects the electric field configuration and the electric field intensity in a cylindrical T M 010 microwave cavity which in turn modifies the absolute electron density value determination. We have carried out the same measurement in the first experimental dual mode set up, for the S-band microwave range.…”
Section: Electron Density Measurementsmentioning
confidence: 97%
“…24 This work showed that errors may range from a few percent to one hundred percent if samples are probed in the iris region.…”
Section: Awmentioning
confidence: 96%
“…In a perfect empty and sealed cylindrical cavity there is no electric field variation in vertical direction. Modelling by Pipiskova & Lukac (1970) At this point the measurement technique diverges. Room temperature measurements only require another measurement of the centre frequency and bandwidth of the resonant modes and then the sample is discarded and the process begins with a fresh sample tube and kaolin-wool plug.…”
Section: Measurement Proceduresmentioning
confidence: 99%